Evaluating Students' Skills in Using the Moodle Platform for Distance Education: A Field Study for Developing E-Learning Strategies in Algerian Universities - Benotmane, Ismahane (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study aimed to assess the extent to which university students possess the skills needed to use the Moodle platform in distance education. The study employed a descriptive approach using a questionnaire consisting of 36 items distributed across four main areas: managing access to the learning environment, learning management, managing participatory activities, and managing assessment activities. The questionnaire was administered to a sample of 163 students (male and female) from Mohamed Lamine Debaghine Setif 2 University. The findings revealed that students possess a moderate level of proficiency in using the Moodle platform for distance learning. However, the results also showed that students face challenges in certain areas, particularly in managing participatory and assessment activities. These findings suggest that distance education in a digital environment requires the promotion of continuous training on the use of educational platforms, in addition to the provision of technical and institutional support to ensure its effectiveness. Based on these results, the study recommends organizing targeted training workshops to strengthen students' skills in effectively using the Moodle platform. It also calls for the involvement of specialists in this field to improve the quality of distance education in universities and to develop educational strategies that promote the optimal use of digital platforms.